Analisis Kualitas Pelayanan E-KTP di Kecamatan Gayamsari Kota Semarang - Rahayu, Ika Puji; Warsono, Hardi; Dwimawanti, Ida Hayu (Journal of Public Policy and Management Review, 2014)
Quality is a condition that shows the correspondence between expected with reality either individuals or groups . Electronic ID card ( e-ID ) is a national identity card ( KTP ) is created electronically , in terms of both the physical and functional use computerized .Subdistrict Gayamsari is one of the organizers of the E - ID card organization in the city of Semarang . This study aims to find out about the quality of service in the District E - KTP Gayamsari Semarang and the factors that support and hinder the quality of e- ID card service.Based on the results of this study concluded that the overall quality of service in the District E - KTP Gayamsari has not done well . It can be seen from the five dimensions of service quality , namely : Tangibles , Reliability, Responsiveness , Assurance and Emphaty . Factors that hamper the quality of service is a factor rules, ability-skills, service facilities.Based on these conclusions , the researchers recommend to Semarang Population and Civil Registration Offices and Gayamsari District Office to improve the indicators assessed to be less successful that the quality of service in the Gayamsari District E - ID card can be well categorized.